Use of lidocaine for treatment of pulseless ventricular tachycardia after massive cocaine overdose. Issue 1 (1st January 2019) - Woolum, Jordan A.; Travis, Matthew; Crane, Cicero Running; Bailey, Abby M.; Baum, Regan A.; Akpunonu, Peter
Abstract: A 35-year-old woman presented to the emergency department in cardiac arrest after ingesting large quantities of powdered cocaine. With an initial rhythm of ventricular fibrillation, emergency medical providers were able to achieve return of spontaneous circulation prior to hospital transport. Shortly after emergency department arrival the patient experienced pulseless electric activity arrest. Despite routine advanced cardiac life support, she remained critically ill and intermittently achieved palpable pulses before returning to pulseless ventricular tachycardia. She received intravenous lipid emulsion and dual defibrillation therapies without clinical improvement. After a lidocaine bolus and intravenous infusion, she had a sustained return of spontaneous circulation. The patient was taken to the intensive care unit before withdrawal of care two days later due to a poor prognosis for recovery.